The biological meaning of preferences on the human mate market - Pawłowski, Bogusław (Polskie Towarzystwo Antropologiczne, 2000)
Factors, which universally influence mate choice decisions, are: age, physical appearance, and resources. Different evidence of the biological relevance of these three factors on the human mate market is presented. The sex-specific preferences for partner's age reflect such values as Fisherian reproductive potential and fecundity for females and life expectancy related to the length of further time of paternal investment for males. Physical attractiveness is analyzed as a marker of female's age, and in the case of both sexes as a marker of hormone level, heterozygosity and therefore immunocompetence. Because attractiveness connotes genetic quality of a prospective partner and indicates higher fitness for offspring, it is not an arbitrary trait. Resources of males are discusssed as being important for females because they assure good paternal investment and therefore hihger reproductive success. Human flexibility in age and physical attractiveness preferences is also examined in relation to ecological conditions. The evidence presented here indicates that the factors influencing human mate choice decisions can be honest, biologically relevant cues of reproductive value of a prospective partner.
Keywords: human mate preferences; reproductive potential; age preferences; physical attractiveness; height; WHR